La lectura a través de pictogramas en educación inicial - Guanoluisa Amores, Mónica Alexandra (2017)
The present research project had the purpose to motivate the children of the "María Montessori" CEI to read through new and innovative ways such as pictograms. This will enable them to develop their skills and skills through the application of strategies, resources, resources and pictographic materials that will contribute to better conduct the teaching-learning processes. When considering that the institution does not exist pictography as strategies within the educational process, which is why it becomes mandatory to implement reading through pictograms to improve the reading quality of children of initial education of the institution With the pictographic methodological implementation, children will be able to develop inter-learning, making classes true teaching processes where the teacher becomes the motivating axis and the child in the circumstantial part, which contributes to the integral development of the same. For the preparation of the document was based on a descriptive research with a non-experimental design based on a method both inductive and deductive analysis and synthesis….